International trade in ICT services: the case of Ukraine - KRASNIKOVA, Наталія; DZYAD, Олена; HRECHYN, Кирило (Ius Modernum, 2020)
Background. Today, the information and communications technology (ICT) sector is one of the most dynamic sectors of the world economy. Since IT services are the second largest export sector in Ukraine, the study of the impact of international trade in ICT services on economic growth becomes relevant. Analysis of recent research and publications. Numerous papers have shown the positive impact of international trade in ICT goods and services on production volumes, employment and productivity of national economies. In particular, UNCTAD data show that the ICT services sector shows an increase in employment and international trade in all geographical regions and provides most of the added value in the ICT sector. The aim of the article is to study the impact of international trade in ICT services on the development of economies of different levels of development, taking into account national policies of ICT sector, and to develop recommendations for Ukrainian policy of ICT sector, taking into account the experience of analyzed countries. Materials and methods. The information base for the study was data from UNCTAD, OECD, Eurostat, and the State Statistics Service of Ukraine. Methods of statistical, structural, regression, comparative analysis are used. Results. Regression analysis was used to identify the relationship between GDP and the volume of exports and imports of ICT services in the analyzed countries. The results showed that in order to ensure economic development through trade in ICT services, countries need to pursue a stimulating policy, which includes measures in three main areas: support for innovation (R&D funding and startup ecosystems); education and training of ICT specialists; and support for investments in ICT services (through preferential taxation and grant schemes). Conclusion. In order to support the growth of the national IT industry, the Ukrainian government is proposed to legalize existing schemes of cooperation of IT companies with private individuals, to avoid additional regulation of the industry, and to develop schemes to financially support innovation in science and business.